Interview with the inspector of education in the province of Huesca Mrs. María José Madonar Pardinilla - Faci Lucia, Fernando; Cabrera Delgado, José Manuel (Avances en Supervisión Educativa, 2020)
María José Madonar Pardinilla has been an education inspector in the province of Huesca (Spain) for more than twenty years. The Huesca Education Inspectorate is made up of twelve inspectors and inspectors who intervene in a territory of 15,626 km2 and 219,702 inhabitants distributed in 202 municipalities in which there are just over 250 educational centers.The professional story of María José Madonar is that of a professional dedicated to her work as a teacher (educational inspection is also a teaching destination). Throughout his career he has published a number of articles far above the average in this profession. Some of them have been published in our magazine. Others can be found in indexers such as Dialnet or on their Researchgate page.From the magazine “Avances en Supervisión educativa” (Advances from now on) we have decided to interview her to publicize her professional career and delve into her day-to-day work, focused on a preferably rural environment. We hope that, with this interview, you can get to know this exciting profession better.